La magie des nombres - Barbette, Edouard (Liège : s.n., 1925)
Bibliotheek Camille Huysmans
Dedicator: Barbette, Edouard, dedicatee: Huysmans, Camille
Autographie Nicolai
Frans
Monografie
Keywords: wetenschappen